Public authorities’ commitment to follow a policy providing ecological safety understoodas a synonym of appropriate quality of the environment - Jaworowicz-Rudolf, Agnieszka (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The author analyzes issues of the constitutional commitment of public authorities to care for the quality of the environment, taking into account future generations. She indicates that the concept of ecological security has not been specified explicitly by the legislator, and the views formulating the right to ecological safety are considered disputable. It was emphasized that the problem of low emission is currently the key challenge for public authorities.